Being Kenyan in the Times of a Crisis: Conflicting National Narratives against COVID-19 - (:unkn) unknown (My University, 2021)
In the face of the deadly COVID-19 pandemic, the Kenyan government developed a national narrative aimed to empower its population and give it the responsibilities the public authorities could not fully handle. Being a Kenyan, officials said, was about being resilient and innovative, and entailed following on in the footsteps of the notorious examples of heroic figures that have been newly erected on that occasion. This ideal-type of the resilient and responsible Kenyan was story-told broadly through an assertive media strategy that President Uhuru Kenyatta and other influential political figures put forward. It was quickly confronted, however, by stark contestations and alternative narratives from civil society. Sometimes newcomers in the public debate, some social activists indeed defined their own heroes and martyrs and insisted on the state’s responsibility to protect its population in times of crisis.
Keywords: African Research